Democratic Participation in the Air Strikes Against Islamic State: A Qualitative Comparative Analysis1. Issue 2 (8th October 2016) - Haesebrouck, Tim
Abstract: Although over sixty partners have joined the US-led coalition against the Islamic State (IS), only a handful of states was willing to carry out air strikes against IS-targets. This article aims to explain the pattern of democratic participation in the air campaign. It builds on the rich literature on military burden sharing and democratic peace theory to develop a multi-causal model, which is tested with Qualitative Comparative Analysis. The results of the analysis suggest that the pattern of participation in the air strikes results from a complex interplay between alliance politics, threat perception and domestic institutional constraints. The threat posed by foreign fighters and a strong interest in a good relationship with the US constituted important incentives to participate in the air strikes, while a high level of parliamentary involvement in military deployment decisions inhibited participation. Furthermore, states that were situated in Russia's immediate vicinity refrained from participating, in spite of their strong dependence on the US' security guarantee. Lastly, the analysis did not provide convincing evidence that partisan politics had an impact on participation in the air strikes.